Living Through the Pandemic: The Voices of Persons With Dementia and Their Caregivers. (January 2022) - Rising, Kristin L.; Salcedo, Venise J.; Amadio, Grace; Casten, Robin; Chang, AnnaMarie; Gentsch, Alexzandra; O'Hayer, C. Virginia; Sarpoulaki, Nazanin; Worster, Brooke; Gerolamo, Angela M.
Social-distancing guidelines from the COVID-19 pandemic have potential to compound morbidity in persons with dementia (PwD) and increase caregiver burden. This qualitative study utilized semi-structured interviews between August-November 2020 to explore the impact of COVID-19 on PwD and caregivers. Conventional qualitative content analysis was used. Inter-coder reliability was confirmed using the kappa coefficient. Twenty-five interviews were completed with four themes emerging: disruption of socialization, fear and risk mitigation, coping strategies, and caregiver burden. Participants described how lack of socialization and confinement led to feelings of loneliness, depression, and worsening memory problems. Caregivers reported increased burden and heightened feelings of responsibility for their loved one. Increased isolation imposed by the pandemic has a detrimental impact on PwD. Further work is needed to develop interventions to support PwD and other cognitive impairments and caregivers during the pandemic and when in-person socialization is not possible.